MANAJEMEN ASUHAN KEBIDANAN PERIMENOPAUSE PADA NY “N” DENGAN MENSTRUASI TIDAK TERATUR DI PUSKESMAS KASSI-KASSI KOTA MAKASSAR TAHUN 2021 - Santi, Nur; Andryani, Zelna Yuni; A. Tihardimanto (Jurnal Midwifery, 2022)
Introduction Perimenopause is a transitional period between premenopause and postmenopause. During the period, natural complaints may occur such as irregular menstruation, hot flushes, and sleeping disorders. Women with irregular menstruation are likely to require midwifery care in order to overcome its various negative effects including anxious feeling, fear, which are normal for perimenopausal women before menopause. The main objective of this research was to investigate perimenopause Midwifery Care Management in Mrs. "N" with Irregular Menstruation at Kassi-Kassi Health Center of Makassar. This research was conducted based on the 7 stages of Varney management approach and SOAP documentation procedure. The findings of this research indicated that Mrs."N" experienced irregular menstruation during her perimenopause. However, there were no obstacles and issues found during the care. The monitoring was carried out 4 times for approximately 2 months in which the major complaint by Mrs N was the irregular menstrual cycles. It was also apparent that she felt hot and had trouble sleeping at night. After she was given care or information related to perimenopause, the patient was no longer complaining and was more receptive to the conditions she experience. Conclusion This research concludes that the 7 stages of Varney manageent approach and SOAP documentation procedure could be used as treatment procedure to overcome the issue related to perimenopause. The management approach and procedure were successfully conducted in which the patient could understand her condition after she was given information and knowledge related to various symptoms of perimenopause.